Using Animation Videos in Developing Listening Skills Among Junior High School Students - Safira, Mutiarasafira; Kamaruddin, Abd; Arid, Muhammad; Aminah, Aminah (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
Listening cannot be underestimated, because listening is an important aspect of communication. In life if someone communicates with others, they must understand what the speaker says in writing and during conversation. This study's objective was to understand how animated videos can enhance individuals' capacity for learning. Pre-tests and post-tests were part of this study's single-group pre-experimental design. The sample was chosen using purposeful sampling. There were seven classes for eighth-grade students. It was from class VIIIA to VIIIG. The total population of class VIII was 220 students. The class selected as the Sample used in this study was class VIIIB, which had 29 students. Test instruments were utilized in this study to gather the score in pre-test and post-test. Twenty fill-in-the-blank and matching questions made up the test. To determine whether using animated video content enhanced students' listening skills, a paired sample t-test was used in the data analysis. The tests outcomes were compared in this investigation. Ha (Alternative Hypothesis) and H0 (Null Hypothesis) were hypotheses in this investigation. The average scores differed significantly, the study's findings. 56.96 was the pre-test score, while the post-test score was 69.96. The significance level was marginally below 0.05, as indicated by the paired sample t-test statistical analysis results, which were significant (two tails) at 0.030. In the end, Ha was accepted and H0 was rejected. Therefore, watching animated films helps children improve their ability to interact with others.